Why migration policies fail - Castles, Stephen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Immigration and asylum are key political issues in Britain and the European Union. Yet the policies of states and supranational bodies seem to have had little success in preventing unwanted flows and effectively managing immigration and integration. This article examines three types of reasons for policy failure: factors arising from the social dynamics of the migratory process; factors linked to globalization and the North-South divide; and factors arising within political systems. Key issues include the role of migrant agency, the way the North-South divide encourages flows, and hidden agendas in national policies. EU efforts to address the root causes of migration in countries of origin are discussed. The article concludes that migration policies might be more successful if they were explicitly linked to long-term political agendas concerned with trade, development and conflict prevention. Reducing North-South inequality is the real key to effective migration management.